Update on the relevance of mechanobiological mechanisms in lung cancer - Antonios N. Gargalionis; Kostas A. Papavassiliou; Efthimia K. Basdra; Athanasios G. Papavassiliou (Translational Oncology)
Lung tumorigenesis is characterized by mechanical perturbations at the molecular level that affect cancer development, progression and drug efficacy. Tumor expansion, alterations in the matrix stiffness and aberrant mechanical inputs lead to distorted mechanobiology of cancer and stromal cells. This dysregulation is accompanied by oncogenic mechanosignaling facilitating their invasion, migration and immune evasion. A growing volume of data highlight that such molecular events are translated to clinical phenotypes, which encompass a distinct group of oncogenic molecular mechanisms, prognostic and predictive biomarkers as well as putative therapeutic targets in lung cancer.